TRANSFORMATION OF TRADITION KUPATAN EID AL-FITR AMONG THE JAVANESE MUSLIM DIASPORA IN MALAYSIA - Ach Hakiki; Dody S Truna; Ilim Abdul Halim; Mochamad Ziaul Haq (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2026)
This study aims to analyze the Eid Kupatan tradition brought by the Javanese Muslim diaspora to Malaysia. The Kupatan tradition is a tradition that existed among Javanese Muslims which was introduced by Sunan Kalijaga during the Demak Kingdom for the Islamization process at that time. The Kupatan tradition is carried out seven days after Eid al-Fitr, in Javanese, ketupat or kupat is interpreted as "Jharwa dhosok" which also means "admit Lepat" that is, one must be able to apologize when one makes a mistake. In the Kupatan tradition, ketupat is the main dish, a rice- based ketupat wrapped in janur or young coconut leaves in a rectangular shape. The presence of the Kupatan tradition in Malaysia was brought about by the Javanese Muslim diaspora community, the local Malaysian community accepted the Kupatan tradition because they have several similarities in tradition, such as language, culture and religion, therefore the Kupatan tradition was well received and produced positive values for Malaysian local community. In its development, the Javanese Muslim Eid Kupatan tradition in the Javanese Muslim diaspora has acculturated, but does not change essential things or the meaning of the tradition, it is evident that the purpose of holding the Eid Kupatan tradition is still in accordance with the original meaning and purpose. The tradition of Eid Kupatan for the Javanese Muslim diaspora in Malaysia has become a separate identity for the Javanese Muslim diaspora, because other Muslim diaspora communities do not do that, and have different characteristics. This research method uses a qualitative approach.